1987
DOI: 10.1007/bf01852051
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the possible involvement of the dopaminergic system in the modulation of the growth and steroidogenic capacity of the rat adrenal zona glomerulosa: A coupled morphometric and biochemical study

Abstract: The effects of metoclopramide (MTC) and bromocriptine (BRC) (two drugs which act as antagonist and agonist of DOPA-receptors, respectively) on the zona glomerulosa of dexamethasone/ACTH-treated rats were investigated by coupled biochemical and morphometric techniques. Short-term (1-h) MTC administration significantly increased the plasma concentration of aldosterone, while long-term (7-day) MTC administration, as well as short- and long-term treatment with BRC did not cause any apparent change. Long-term MTC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
3
2
0
Order By: Relevance
“…Our results also confirm the contention that an increase in angiotensin II production is not the sole mechanism whereby prolonged sodium deprivation stimulates the growth of rat ZG [15]. In fact, we used animals in which the renin-angiotensin system had been pharmacologically interrupted by captopril, an inhibitor of the angiotensin-converting enzyme [19].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results also confirm the contention that an increase in angiotensin II production is not the sole mechanism whereby prolonged sodium deprivation stimulates the growth of rat ZG [15]. In fact, we used animals in which the renin-angiotensin system had been pharmacologically interrupted by captopril, an inhibitor of the angiotensin-converting enzyme [19].…”
Section: Discussionsupporting
confidence: 88%
“…In fact, we used animals in which the renin-angiotensin system had been pharmacologically interrupted by captopril, an inhibitor of the angiotensin-converting enzyme [19]. We previously suggested that the suppression of the dopaminergic system may be involved in the enhancement of the growth and secretory capacity of the ZG of sodium-restricted rats [15]. The present data indicating that dopamine infusion completely reverses the effects of sodium restriction on the ZG strengthen this hypothesis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Restriction of dietary sodium intake causes hypertrophy of the zona glomerulosa and its parenchymal cells, which is reflected in an increased capacity for aldosterone secretion, and elevated plasma aldosterone concentrations (Mazzocchi et al, 1987;Mü ller, 1989;Quinn and Williams, 1988;Vinson et al, 1992). These changes are at least partially mediated by the circulating RAS (Aguilera and Catt, 1978;Aguilera et al, 1978;Ganong et al, 1966;Williams and Dluhy, 1972), but additionally by a discrete glomerulosa RAS system (Mulrow, 1992;Phillips et al, 1993).…”
Section: Introductionmentioning
confidence: 99%